Antibacterial Activities of Red Flow Oil (Piper Crocatum Ruiz & Pav.) in The Form of Emulsion and Microemulsi - Elsa Putri Kartika; Marchaban Marchaban; Sudarsono Sudarsono (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
The red sirih essential oil (RSEO) known has antibacterial activity and can be obtained by water and steam distillation of red betel leaf (Piper crocatum Ruiz & Pav.). The aim of this study is to compare its bacterial activity if the RSEO is formulated in different dosage forms (i.e. emulsion and microemulsion). The RSEO in emulsion dosage form was prepared by stirring 0.875 g of liquid paraffin, 0.125 g RSEO, 0.125 g of tween-80, 0.375 g of span-80 (HLB 7), and 3.500 g of water. The RSEO in microemulsion dosage form was prepared by stirring 0.125 g of liquid paraffin, 0.125 g RSEO, 0.417 g Tween 80, 0.833 g of PEG-400 and 3.500 g of water. Antibacterial activity against Escherichia coli ATCC 25922 was done by using microdilution method at 1% of w/w concentration using the ELISA reader at 570 nm. The data was then to be analysed to compare the percentage of inhibition of the bacterial growth. The results showed that the bacterial inhibition of RSEO in emulsion dosage form was 17.45±5.9% while in microemulsion dosage form was 49.58±3.27%. It is concluded that the RSEO had a better antibacterial activity in the forms of microemulsion than emulsion.